2019
DOI: 10.1101/598540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Misfolded amyloid β-42 induced impairment of the endosomal-lysosomal pathway revealed by real-time optical monitoring

Abstract: Misfolding and aggregation of proteins is strongly linked to several neurodegenerative diseases but how such species bring about their cytotoxic actions remains poorly understood. Here we used specifically-designed optical reporter probes and live fluorescence imaging in primary hippocampal neurons to characterise the mechanism by which prefibrillar, oligomeric forms of the Alzheimer's-associated peptide, Aβ42, exert their detrimental effects. We used a pH-sensitive reporter, Aβ42-CypHer, to track Aβ internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
2
0
0
Order By: Relevance
“…[32] We also measured Aβ1-42 on cell viability in primary hippocampal neurons by using the Ready-probes assay. [33] Compared with the DMSO-treated neurons, neurons incubated with both 5-and 10-μM Aβ1-42 oligomers showed significantly lower viability (Figure S1A-D), consistent with previous studies. [33] We quantified the components of Aβ preparation by Western blot (Figure S1E) and found that the major oligomer was trimer, which accounted for about 5% of the total mass (Figure S1F).…”
Section: Aβ1-42 Treatment Alters the Nanoscale Organisation Of Synapt...supporting
confidence: 91%
See 1 more Smart Citation
“…[32] We also measured Aβ1-42 on cell viability in primary hippocampal neurons by using the Ready-probes assay. [33] Compared with the DMSO-treated neurons, neurons incubated with both 5-and 10-μM Aβ1-42 oligomers showed significantly lower viability (Figure S1A-D), consistent with previous studies. [33] We quantified the components of Aβ preparation by Western blot (Figure S1E) and found that the major oligomer was trimer, which accounted for about 5% of the total mass (Figure S1F).…”
Section: Aβ1-42 Treatment Alters the Nanoscale Organisation Of Synapt...supporting
confidence: 91%
“…[33] Compared with the DMSO-treated neurons, neurons incubated with both 5-and 10-μM Aβ1-42 oligomers showed significantly lower viability (Figure S1A-D), consistent with previous studies. [33] We quantified the components of Aβ preparation by Western blot (Figure S1E) and found that the major oligomer was trimer, which accounted for about 5% of the total mass (Figure S1F). Meanwhile, the immunostaining showed that a significant fraction of Aβ was colocalised with PSD-95, suggesting its direct targeting to synapses (Figure S1G-I).…”
Section: Aβ1-42 Treatment Alters the Nanoscale Organisation Of Synapt...supporting
confidence: 91%